Cost-effectiveness of screening for the possible development of cancer in patients with oral lichen planus - van der Meij EH, Bezemer PD, van der Waal I. (Blackwell Synergy, 2002)
Several authors have expressed the view that patients with oral lichen planus (OLP) are at increased risk of developing oral cancer.